A validation of the National Early Warning Score to predict outcome in patients with COPD exacerbation. Issue 1 (23rd August 2016) - Hodgson, Luke E; Dimitrov, Borislav D; Congleton, Jo; Venn, Richard; Forni, Lui G; Roderick, Paul J
Abstract : Background: The National Early Warning Score (NEWS), proposed as a standardised track and trigger system, may perform less well in acute exacerbation of COPD (AECOPD). This study externally validated NEWS and modifications (Chronic Respiratory Early Warning Score (CREWS) and Salford-NEWS) in AECOPD. Methods: An observational cohort study (2012–2014, two UK acute medical units (AMUs)), compared AECOPD (2361 admissions, 942 individuals, International Statistical Classification of Diseases and Related Health Problems-10 J40–J44 codes) with AMU patients (37 109 admissions, 20 415 individuals). Outcome: In-hospital mortality prediction was done by admission NEWS, CREWS and Salford-NEWS assessed by discrimination (area under receiver operating characteristic curves (AUROCs)) and calibration (plots and Hosmer-Lemeshow (H-L) goodness-of-fit). Results: Median admission NEWS in AECOPD was 4 (IQR 2–6) versus 1 (0–3) in AMUs (p≤0.001), despite mortality of 4.5% in both. AECOPD AUROCs were NEWS 0.74 (95% CI 0.66 to 0.82), CREWS 0.72 (0.63 to 0.80) and Salford-NEWS 0.62 (0.53 to 0.70). AMU NEWS AUROC was 0.77 (0.75 to 0.78). At threshold NEWS=5 for AECOPD (44% of admissions), positive predictive value (PPV) of death was 8% (5 to 11) and negative predictive value (NPV) was 98% (97 to 99) versus AMU patients PPV of 17% (16 to 19) and NPV of 97% (97 to 97). For NEWS in AECOPD H-L p value=0.202. Conclusion: This first validation of the NEWS in AECOPD found modest discrimination to predict mortality. Lower specificity of NEWS in patients with AECOPD versus other AMU patients reflects acute and chronic respiratory physiological disturbance (including hypoxia), with resultant low PPV at NEWS=5. CREWS and Salford-NEWS, adjusting for chronic hypoxia, increased the specificity and PPV but there was no gain in discrimination.